2014
DOI: 10.1111/vco.12118
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of microRNA‐203 function in CREB/MITF/RAB27a pathway: comparison between canine and human melanoma cells

Abstract: MicroRNA (miR)-203 is downregulated and acts as an anti-oncomir in melanoma cells. Here, using human and canine melanoma cells, we elucidated the effects of miR-203 on cyclic adenosine monophosphate response element binding protein (CREB)/microphthalmia-associated transcription factor (MITF)/RAB27a pathway, which is known to be important for the development and progression of human melanoma. In this study, we showed that miR-203 directly targeted CREB1 and regulated its downstream targets, MITF and RAB27a. miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 33 publications
0
18
0
2
Order By: Relevance
“…During the last years miRs have been identified, which are deregulated by CREB or have CREB as direct target due to binding to its regulatory sequences at the 3′-UTR (Table 1). Using in silico prediction by different algorithms CREB expression could be regulated by different miRs known to be frequently downregulated in tumors, such as miR-181b, miR-128, miR-124, miR-34b, miR-23a, miR-200b, miR-203 and miR-301 [21, 4649]. In some studies luciferase reporter assays confirmed the interaction of these miRs with the 3′-UTR of CREB.…”
Section: Molecular Basis Of Creb Regulationmentioning
confidence: 99%
“…During the last years miRs have been identified, which are deregulated by CREB or have CREB as direct target due to binding to its regulatory sequences at the 3′-UTR (Table 1). Using in silico prediction by different algorithms CREB expression could be regulated by different miRs known to be frequently downregulated in tumors, such as miR-181b, miR-128, miR-124, miR-34b, miR-23a, miR-200b, miR-203 and miR-301 [21, 4649]. In some studies luciferase reporter assays confirmed the interaction of these miRs with the 3′-UTR of CREB.…”
Section: Molecular Basis Of Creb Regulationmentioning
confidence: 99%
“…Interestingly, as assessed by RT-qPCR, Western blotting, and luciferase reporter assay, CREB1 was identified as a direct target of miR-203 in a multiple myeloma model ( Figure 5) [55]. Of note, this specific targeting was further confirmed by Noguchi et al in canine and human melanoma cells [159]. BMP-2 and TGF-β are able to modulate the expression of the secreted protein acidic and rich in cysteine matrix-associated protein (SPARC/osteonectin).…”
Section: The Bone Morphogenetic Proteins (Bmp) Pathwaymentioning
confidence: 76%
“…In addition, we confirmed that miR‐203 directly targeted SRC (Figure S1A‐C, Supporting Information). Earlier, we have reported that miR‐203 is downregulated and acts as an anti‐oncogene in melanoma cells . Therefore, SRC is considered to be not only activated but also possibly be overexpressed in canine and human melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, SRC is known to be a target gene of anti‐oncogenic microRNA (miR)‐203 in several kinds of human cancers . Recently, we reported that miR‐203 is downregulated by DNA methylation and exhibits anti‐oncogenic functions in melanoma cells . Based on these findings, we hypothesized that SRC is overexpressed and a promising therapeutic target in melanoma.…”
Section: Introductionmentioning
confidence: 99%